2013
DOI: 10.1016/j.drugalcdep.2012.06.004
|View full text |Cite
|
Sign up to set email alerts
|

High-sensitivity gamma-glutamyltransferase fraction pattern in alcohol addicts and abstainers

Abstract: Background: Four fractions of gamma-glutamyltransferase (GGT) with different molecular weight (b-, m-, sand nd f-GGT) are present in human plasma. Differential GGT fraction pattern is found in non-alcoholic liver disease (NAFLD) and chronic viral hepatitis, characterized by normal or decreased b-GGT/s-GGT (b/s) ratio, respectively. Methods: Chromatographic fractional GGT analysis was performed on plasma obtained from 51 subjects: 27 alcoholics (mean (SD), age 45 (9) years; 23 males; 14 positive for viral infec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 11 publications
2
21
0
2
Order By: Relevance
“…Methods for measuring subfractions of total GGT activity (i.e., s-GGT, m-GGT, b-GGT and f-GGT) have been reported by Franzini et al [24], and disease-specific patterns of GGT subfractions and ratios of subtypes are emerging, for example, increased b-GGT has recently been associated with cardiovascular risk [27], whereas s-GGT was increased in alcoholics [39]. Our research is limited by not having this GGT subfraction data, which should be applied in future studies to better differentiate subgroups within larger cohorts by disease status, including those with isolated hepatic disease and those with multiorgan disease, that is, concomitant nonalcoholic fatty liver disease, metabolic disease and cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods for measuring subfractions of total GGT activity (i.e., s-GGT, m-GGT, b-GGT and f-GGT) have been reported by Franzini et al [24], and disease-specific patterns of GGT subfractions and ratios of subtypes are emerging, for example, increased b-GGT has recently been associated with cardiovascular risk [27], whereas s-GGT was increased in alcoholics [39]. Our research is limited by not having this GGT subfraction data, which should be applied in future studies to better differentiate subgroups within larger cohorts by disease status, including those with isolated hepatic disease and those with multiorgan disease, that is, concomitant nonalcoholic fatty liver disease, metabolic disease and cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the potential to improve upon our methods by subfractionating GGT, the associations demonstrated here with total serum GGT activity remain valid. Other studies have demonstrated that participants with increased total serum GGT activity have increased GGT subfractions more associated with disease (i.e., non-f-GGT fractions), total serum GGT activity increased with increases in each subfraction (i.e., except f-GGT) and total serum GGT activity remains the most accessible biomarker to clinicians [26,27,39]. …”
Section: Discussionmentioning
confidence: 99%
“…Metabolic and cardiovascular risk markers are important correlates of GGT fractions, in particular of b-GGT in healthy subjects [42] and in Framingham population [43]. It is noteworthy that non-alcoholic fatty liver disease, a component of the metabolic syndrome which is associated to increased cardiovascular risk [44], seems to be a rather specific cause of plasma b-GGT increase in blood [45], while alcohol abuse and liver diseases are more specifically associated with s-GGT elevation [46].…”
Section: Intra-plaque B-ggtmentioning
confidence: 99%
“…While f-GGT is the major circulating GGT fraction in healthy subjects in both sexes, in the pathological conditions examined so far, b-GGT and s-GGT accounted for most of total GGT increase [26-27]. Chronic viral hepatitis C [26] and alcoholic-liver disease [27] are characterized by the increase in s-GGT and the decrease in the b-GGT/s-GGT (b/s) ratio.…”
Section: Introductionmentioning
confidence: 99%